2009
DOI: 10.1002/er.1499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementary firing options on cycle performance and CO2emissions of an IGCC power generation system

Abstract: SUMMARYSupplementary firing is adopted in combined-cycle power plants to reheat low-temperature gas turbine exhaust before entering into the heat recovery steam generator. In an effort to identify suitable supplementary firing options in an integrated gasification combined-cycle (IGCC) power plant configuration, so as to use coal effectively, the performance is compared for three different supplementary firing options. The comparison identifies the better of the supplementary firing options based on higher eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Due to the immense increase in temperature from the subcritical case to the supercritical case, a duct burner is necessary to raise the temperature of the steam entering the steam turbine to the appropriate level. Therefore, the plant must make use of natural gas as a substitute fuel in order to achieve this high temperature. Both cases are shown in Figures and , respectively, both using 0% biomass in the feedstock.…”
Section: Design Methodsmentioning
confidence: 99%
“…Due to the immense increase in temperature from the subcritical case to the supercritical case, a duct burner is necessary to raise the temperature of the steam entering the steam turbine to the appropriate level. Therefore, the plant must make use of natural gas as a substitute fuel in order to achieve this high temperature. Both cases are shown in Figures and , respectively, both using 0% biomass in the feedstock.…”
Section: Design Methodsmentioning
confidence: 99%
“…Research investigations are conducted on IGCC systems to further improve their performance. Gnanapragasam et al, [5] reported the performance analysis for a coal gasification combined cycle power generation system as shown in Figure 2. There is also growing interest to develop IGCC systems with carbon capture and also with hydrogen production [6,7].…”
Section: B Coal Biomass Gasification and Combined Cycle Power Genermentioning
confidence: 99%
“…The economic viabilities of IGCC power plants with CO 2 capture has however been widely studied, along with several process configurations and feedstocks [15][16][17][18]. The pertinent published studies have covered the COE analysis for the performance of an IGCC power plant with Carbon Capture and Storage (CCS) with respect to several input parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%